Discriminações condicionais em bebês de risco: o responder por exclusão - Sertori, Natália Maria (2013)
Exclusion responding has been investigated as the immediate choice for unknown comparison stimuli (picture or object) facing a model stimulus also unknown. For Behavior Analysis, it is one of the processes by which children learn to relate new words to new objects or new events. This process has been extensively investigated under experimental conditions and is usually based on studies made by the teaching of "conditional discrimination" with the technique of matching to sample. Considering the advances in literature, the present study aimed to investigate exclusion responding in infants aged between 13 and 20 months, with indicators of difficulties in language acquisition. Data collection began by teaching familiar conditional relations in base lines, using familiar stimuli. After the establishment of such relations, tests of exclusion, control and learning with familiar insertion using objects intercalated between the base lines were conducted. The results demonstrated the repeatability of the procedure, seen in previous studies, through which the population of young children respond by exclusion and some show, after being exposed to more than one attempt, they learn to relate word-object. Control probes showed that all babies responded under control of the topography of selection and rejection in different attempts. Two participants demonstrated control only by selection in all attempts. The procedure was terminated either if the baby hit the learning probe or after a maximum of two sessions with five attempts. One can assume that this study brings an important variable - the investigation of the control of responding by exclusion, with babies from this age group - using the "teaching notebook" as storage apparatus, in hopes to bring about a more natural environment for the child, in order to not to cause "strangeness" to the little ones, besides all methodological difficulties that audience brings. In the present study, emphasis was given to the teaching procedures of exclusion responding to babies at developmental risk, younger than populations previously studied, in order that studies with small children in the language acquisition phase can contribute to the proposition of further studies for the improvement of language teaching procedures.